Transceptores MIMO em sistemas de comunicações móveis sem fio com multipontos coordenados - Caldas, Francisco Márcio Correia (2012)
In this work, we evaluated the performance of MIMO (Multiple-Input-Multiple-Output) transceivers on a new architecture proposed to mobile wireless communications systems of next generation XG (Next Generation), denoted by CoMP (Coordinate Mult-Point), which is compared with a co-located architecture, whose user equipments utilize the resources uniquely of the radio base station, which is located. In order to obtain spatial multiplexing gains, diversity and intermediate gains (between the two possible gains), adopts MIMO transceivers, which are submitted to different scenarios: Scenario 1, is composed of a co-located cell, whose coverage area is equivalent to three cooperative cells and Scenario 2, where the co-located cell has the same cooperative cell sizes. In both cases, CoMP architectures and co-located are addressed and evaluates the comparative performance between these scenarios, related to the two architecture. The current analysis is divided into two parts: a systemic character, where observes the SINR (Signal to Interference plus Noise Ratio) behavior with the use of VBLAST (Vertical-Bell Labs Space-Time) and STBC (Space-Time Block Codes) transceivers, the another one, of link character, which uses a hybridMIMO transceiver G2+1, in oder to provide an analysis of the bit error rate. The results show that by means of cooperation, a performance similar to the scenario co-located can be obtained with a smaller number of antennas at base stations, representing a saving in terms of capital expenditure CAPEX (Capital Expenditure) and operational OPEX (Operational Expenditure) network, as well as, a reduction in the error rate.